2022
DOI: 10.1071/cp21558
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of

Abstract: Phenylalanine ammonia lyase (PAL) is the first enzyme in the phenylpropanoid pathway and plays a critical role in plant growth, development and stress defence. However, there have been few reports of the PAL gene family in lucerne (also known as alfalfa, Medicago sativa L.), one of the most important forage legume species worldwide. In this study, we report that PAL in lucerne is encoded by a family of seven genes: MsPAL1–MsPAL7. Furthermore, a comprehensive genome-wide bioinformatics analysis of the MsPAL gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Several data sources suggest that overexpression of specific PAL gene members can activate the defense mechanisms and promote the functional improvement of plants under abiotic stresses. For instance, salinity stress was reported to induce the upregulation of PAL6 in the roots of Medicago sativa [63] and PAL1 in leaves of two Salvia species, consequently increasing total phenolic accumulation [64]. Thus, our results confirm PAL as an indicator of stress conditions in plant species.…”
Section: Discussionsupporting
confidence: 79%
“…Several data sources suggest that overexpression of specific PAL gene members can activate the defense mechanisms and promote the functional improvement of plants under abiotic stresses. For instance, salinity stress was reported to induce the upregulation of PAL6 in the roots of Medicago sativa [63] and PAL1 in leaves of two Salvia species, consequently increasing total phenolic accumulation [64]. Thus, our results confirm PAL as an indicator of stress conditions in plant species.…”
Section: Discussionsupporting
confidence: 79%
“…Members of the PAL gene family have been identified and extensively studied in many plants. The PAL gene family typically comprises 4–15 members, which varies between species, including alfalfa, 11 walnut, 35 potato, 6 and grape. 12 The small difference in the number of members in the PAL gene family indicates that PAL genes did not undergo significant amplification during species differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Different PAL family members contain different numbers and types of elements, indicating that GbPAL genes are involved in different biological regulatory processes, and different PAL genes have specific regulatory patterns. Many studies have shown that PAL genes are involved in responses to environmental stimuli, including stress conditions such as UV exposure, 1 drought, 38 waterlogging, 11 pathogens, wounds, and extreme temperatures. Individual PAL proteins may be structurally distinct from other PALs and appear to have different functions, making PAL a multifunctional gene family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylalanine ammonia-lyase ( PAL ) is a key enzyme in the phenylalanine metabolic pathway of plants [ 9 ]. It plays a crucial role in plant growth, development and resistance to biotic and abiotic stresses [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%